Band alignment of HfAlO/GaN (0001) determined by X-ray photoelectron spectroscopy : effect of in situ SiH4 passivation - Liu, Xinke (2015)
The energy band alignment between HfAlO and GaN (0001) was characterized using high-resolution x-ray photoelectron spectroscopy (XPS). The HfAlO was deposited using a metal-organic chemical vapor deposition (MOCVD) gate cluster. A valence band offset of 0.38 eV and a conduction band offset of 2.22 eV were obtained across the HfAlO/GaN heterointerface without any passivation. With in situ SiH4 passivation (vacuum anneal+SiH4 treatment) on the GaN surface right before HfAlO deposition, the valence band offset and the conduction band offset across the HfAlO/GaN heterointerface were found to be 0.51 eV and 2.09 eV, respectively. The difference in the band alignment is believed to be dominated by the core level up-shift or chemical shift in the GaN substrate as a result of different interlayers (ILs) formed by the two surface preparations.